Management of Genetic Syndromes 2010
DOI: 10.1002/9780470893159.ch40
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis Imperfecta

Abstract: Skeletal deformity and bone fragility are the hallmarks of the brittle bone dysplasia osteogenesis imperfecta. The diagnosis of osteogenesis imperfecta usually depends on family history and clinical presentation characterized by a fracture (or fractures) during the prenatal period, at birth or in early childhood; genetic tests can confirm diagnosis. Osteogenesis imperfecta is caused by dominant autosomal mutations in the type I collagen coding genes (COL1A1 and COL1A2) in about 85% of individuals, affecting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 83 publications
1
30
0
2
Order By: Relevance
“…reported that muscle atrophy in mice due to surgical denervation was not protected by soluble ActRIIB treatment, suggesting increased muscle mass and force via myostatin inhibition may not be effective when there is deterioration of the neuromuscular junction . Muscle atrophy and/or weakness in OI has generally been attributed to immobilization, secondary impacts of neurological impairment or orthopedic casting, and prolonged bed rest due to fractures …”
Section: Discussionmentioning
confidence: 99%
“…reported that muscle atrophy in mice due to surgical denervation was not protected by soluble ActRIIB treatment, suggesting increased muscle mass and force via myostatin inhibition may not be effective when there is deterioration of the neuromuscular junction . Muscle atrophy and/or weakness in OI has generally been attributed to immobilization, secondary impacts of neurological impairment or orthopedic casting, and prolonged bed rest due to fractures …”
Section: Discussionmentioning
confidence: 99%
“…To correct for bowing of the long bones, intramedullary rods are inserted in the bone marrow canal to enhance stability and bone alignment [51,52]. Risk of scoliosis in children with the mildest form of OI is 10-fold greater than in the general population [9] and more common even in OI types III and IV [53]. Progression of scoliosis can lead to pulmonary insufficiency [53,54].…”
Section: Treatmentmentioning
confidence: 99%
“…Risk of scoliosis in children with the mildest form of OI is 10-fold greater than in the general population [9] and more common even in OI types III and IV [53]. Progression of scoliosis can lead to pulmonary insufficiency [53,54]. For best results, corrective surgery through spinal fusion should be sought when curvature is below 60° [53].…”
Section: Treatmentmentioning
confidence: 99%
“…Based on clinical signs the first OI classification from David Sillence (created in 1979) distinguished four types of the disease (I-IV). In the past, related to the development methods of analysis, such as molecular-genetic techniques and histological findings, new forms were identified in the IV group of OI -OI type V-IX [13]. The disease exhibits a wide spectrum of clinical and radiological signs and varies in severity from mild to perinatal lethal forms.…”
Section: Osteogenesis Imperfecta Classificationmentioning
confidence: 99%
“…It is composed of two alpha1(I) chains (encoded by COL1A1 gene) and one al-pha2(I) chain (encoded by COL1A2 gene). The mutations of these two genes have the result in decreased production of the protein or in synthesis of structurally defective collagen molecules [13].…”
Section: Introductionmentioning
confidence: 99%